Decide & deliver : 5 steps to breakthrough performance in your organization - Blenko, Marcia W.; Mankins, Michael C.; Rogers, Paul, 1958- (Boston, Mass. : Harvard Business Review Press, 2010)
Many organizations don't know how to make and execute good decisions. In this book, the authors draw on Bain & Company's extensive research and experience to present a five-step process for improving your company's decision abilities.--[book jacket]
Decisions and results -- Score your organization's decision abilities -- Focus on the decisions that matter most -- Make individual decisions work -- Build an organization that can decide and deliver -- Embed decision capabilities.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Decision making; Problem solving; Organizational change; Decision Making, Organizational; Problem Solving; Organizational Innovation; Decision making; Organizational change; Problem solving; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books